Copper etching solution and preparation method and etching method thereof

By preparing a copper etching liquid containing a specific component ratio, the instability and incomplete etching problems in the prior art etching of the copper and titanium composite film layer are solved, and good etching profile and efficient etching performance are achieved, thereby avoiding damage to the glass substrate or silicon layer.

CN119753686APending Publication Date: 2025-04-04SHANGHAI SHENGJIAN MICROELECTRONICS CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411961997.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, when etching a combined film layer of copper and titanium, it is difficult to form a good etch profile, and there are problems of instability, incomplete etching, titanium residues and titanium tailings, and it is easy to destroy the glass substrate or silicon layer.

Method used

A copper etching liquid is provided, and its components include hydrogen peroxide, metal inhibitors, malonic acid, inorganic salts, chelating agents, fluorides, stabilizers and sodium dodecylbenzenesulfonate. By controlling the proportion and addition order of these components, a copper etching liquid with good stability and high efficiency etching performance is prepared.

Benefits of technology

The copper etching liquid can effectively improve the problems of incomplete etching, titanium residue and titanium tailing, form a good etching profile, and not easily destroy the glass substrate or silicon layer, improve the stability and efficiency of etching, and save the amount of etching liquid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217729640000141
    Figure BDA0005217729640000141
  • Figure BDA0005217729640000142
    Figure BDA0005217729640000142
  • Figure BDA0005217729640000151
    Figure BDA0005217729640000151
Patent Text Reader

Abstract

The present invention relates to the field of etching technology. Specifically, it relates to a copper etching solution, its preparation method, and an etching method. The raw materials of the copper etching solution include: hydrogen peroxide, metal inhibitor, malonic acid, inorganic salt, chelating agent, fluoride, stabilizer, sodium dodecylbenzenesulfonate; the balance is water; the pH of the copper etching solution is: 1.5 < pH ≤ 2. The present invention adopts a low hydrogen peroxide system, which will not cause the rapid decomposition of hydrogen peroxide due to excessive copper ions, thus leading to problems such as rapid temperature rise or even boiling over of the etching solution. This copper etching solution can be used to etch a combined film layer of copper and titanium. It has good stability, can etch to form a good etching profile, can also improve the problems of incomplete etching, titanium residue, and titanium tailing, and is not easily damaged to the glass substrate and the silicon layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of etching, in particular to a copper etching solution and a preparation method and an etching method thereof. Background Art

[0002] In the process of preparing semiconductor devices, it is necessary to form metal wiring on the substrate. The preparation process of forming metal wiring generally includes: forming a metal film on the substrate by using processes such as sputtering, and then coating, exposing and developing in the selected area, and then etching, etc. Among them, the etching methods include dry etching using plasma and wet etching using etching solution.

[0003] The requirements for wet etching generally include the following: high processing accuracy; less etching residue; uniform etching; moderate etching speed; the cross-sectional shape of the wiring formed after etching is within the specified range (for example: the angle (cone angle) formed by the etching surface of the copper wiring end and the underlying substrate is a positive cone shape of 30° to 60°, and the distance from the end of the anti-etching layer to the end of the wiring in contact with the barrier film arranged under the wiring (CD loss) is less than 1.2μm, etc.).

[0004] The wiring materials of some semiconductor devices (for example, display devices such as flat panel displays) usually use copper and copper-containing alloys, which are low-resistance materials. However, since copper has insufficient adhesion to glass substrates and copper has the property of diffusing into silicon semiconductor films, a barrier metal layer such as a titanium layer or a molybdenum layer is usually provided between the substrate and the copper layer wiring as a barrier film to improve the adhesion between the copper layer wiring and the glass substrate and prevent copper from diffusing into the silicon semiconductor film.

[0005] When etching a double-layer metal film composed of a copper layer and a titanium layer, it is usually necessary to mix two different etching solutions to achieve etching of the copper layer and the titanium layer. However, the method of mixing the etching solution for etching the copper layer and the etching solution for etching the titanium layer is difficult to form a good etching profile, and there is an instability problem, which is prone to incomplete etching, resulting in titanium residue and titanium tailing problems, and it is also easy to damage the glass base or silicon layer. Summary of the invention

[0006] The invention aims to provide a copper etching solution and a preparation method and an etching method thereof. The copper etching solution can be used to etch a composite film layer of copper and titanium, has good stability, can form a good etching profile by etching, can improve the problems of incomplete etching, titanium residue and titanium tailing, and is not easy to damage a glass base and a silicon layer; the preparation method of the copper etching solution is simple and easy to operate; the etching method of the copper etching solution can perform etching efficiently and can save the amount of etching solution.

[0007] The present invention is achieved in that:

[0008] In a first aspect, the present invention provides a copper etching solution, wherein the raw materials of the copper etching solution include, by mass percentage:

[0009] 5.00 wt% to 10.00 wt% of hydrogen peroxide;

[0010] 0.05 wt% to 3.00 wt% of a metal inhibitor;

[0011] 5.00 wt% to 15.00 wt% of malonic acid;

[0012] 0.05wt% to 3.00wt% of an inorganic salt;

[0013] 0.05wt% to 5.00wt% of a chelating agent;

[0014] 0.05wt% to 2.00wt% of fluoride;

[0015] 0.05wt% to 10.00wt% of a stabilizer;

[0016] 0.05wt% to 1.00wt% of sodium dodecylbenzene sulfonate;

[0017] The balance is water;

[0018] The pH of copper etching solution is: 1.5 <pH≤2。

[0019] In an optional embodiment, the mass percentage of the metal inhibitor is 0.05wt% to 2.00wt%; and / or,

[0020] The mass percentage of the chelating agent is 0.05wt% to 2.00wt%; and / or,

[0021] The mass percentage of the stabilizer is 0.05wt% to 8.00wt%; and / or,

[0022] The mass percentage of malonic acid is 6.00wt%; and / or,

[0023] The mass percentage of sodium dodecylbenzenesulfonate is 0.5wt%.

[0024] In an optional embodiment, the metal inhibitor includes at least one of 5-methyl-1H-tetrazole, 5-aminotetrazole, benzotriazole, tolyltriazole, pyrazole, pyrrole, imidazole, 2-methylimidazole, 2-ethylimidazole, 2-propylimidazole, 2-aminoimidazole, 4-methylimidazole, 4-ethylimidazole and 4-propylimidazole; and / or,

[0025] The inorganic salt comprises at least one of ammonium hydrogen sulfate, ammonium dihydrogen phosphate, disodium hydrogen phosphate and dipotassium hydrogen phosphate; and / or,

[0026] The chelating agent comprises at least one of free asparagine, iminodiacetic acid, ethylenediaminetetraacetic acid, 2,4-imidazolidinedione, succinimide, glutarimide, glutamic acid, aspartic acid, pyroglutamic acid and hippuric acid; and / or,

[0027] The fluoride comprises at least one of hydrofluoric acid, ammonium fluoride, ammonium bifluoride, sodium bifluoride and potassium fluoride; and / or,

[0028] The stabilizer includes at least one of diethylene glycol, dipropylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 1,4-butylene glycol, and 1,5-pentanediol.

[0029] In alternative embodiments, the inorganic salt comprises ammonium bisulfate and ammonium dihydrogen phosphate.

[0030] In an optional embodiment, the weight ratio of ammonium hydrogen sulfate to ammonium dihydrogen phosphate is 1:1 to 1:1.5.

[0031] In an alternative embodiment, the metal inhibitor comprises at least one of 5-methyl-1H-tetrazole, 5-aminotetrazole and benzotriazole; and / or,

[0032] The chelating agent comprises at least one of iminodiacetic acid, ethylenediaminetetraacetic acid and succinimide; and / or,

[0033] The fluoride comprises at least one of ammonium fluoride and ammonium bifluoride; and / or,

[0034] The stabilizer includes at least one of diethylene glycol, dipropylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, and 1,4-butylene glycol.

[0035] In an alternative embodiment, the stabilizer includes at least one of diethylene glycol, dipropylene glycol, and 1,4-butanediol.

[0036] In a second aspect, the present invention also provides a method for preparing a copper etching solution, comprising: sequentially adding fluoride, an acidic composition, a metal inhibitor, a chelating agent, a stabilizer, water and hydrogen peroxide, and stirring; wherein the acidic composition comprises malonic acid, an inorganic salt and sodium dodecylbenzene sulfonate.

[0037] In a third aspect, the present invention further provides an etching method, comprising: allowing any of the above copper etching solutions to be circulated and sprayed on a substrate to be etched under a preset temperature condition.

[0038] In an optional embodiment, the preset temperature is 25°C to 35°C.

[0039] The present invention includes the following beneficial effects:

[0040] The hydrogen peroxide (H2O2) in the copper etching solution provided by the embodiment of the present invention is used as a main oxidant, which can play a role in forming a conical surface for the copper-titanium metal film during etching; the content of hydrogen peroxide is 5.00wt% to 10.00wt%, which can provide a suitable oxidation effect to ensure a good etching rate, avoid the problem that the etching rate is low and sufficient etching cannot be achieved, or the etching rate may be too fast and the etching degree is difficult to control, resulting in over-etching of the copper-titanium metal film; and, by controlling the amount of hydrogen peroxide, the copper etching solution is a low hydrogen peroxide system, and the problem that the hydrogen peroxide is rapidly decomposed due to excessive copper ions, thereby causing the etching solution to rapidly heat up or even boil violently, will not occur.

[0041] The metal inhibitor can play a role in regulating the etching speed of the copper-titanium metal film, and can improve the stability of repeated use of the copper etching solution for etching, that is, as the number of substrates with metal wiring etched by the copper etching solution increases, the side etch (S / E) can be reduced, and the side etch variation between each substrate is small, which ensures the etching effect and improves the etching efficiency. The content of the metal inhibitor is 0.05wt% to 3.00wt%, which can improve the problem of over-etching caused by too fast etching rate, and also improve the problem of too slow etching rate and reduced efficiency.

[0042] Malonic acid, as an organic acid, is conducive to maintaining the target angle (cone angle) formed by the etching surface of the copper wiring end and the substrate of the lower layer. Malonic acid can also play the role of a co-oxidant, and the content is controlled at 5.00wt% to 15.00wt% to effectively control the etching rate; wherein, by adding malonic acid, the copper ions etched from the copper layer can be more easily dissolved in the copper etching solution, that is, the solubility of the copper ions is increased, which is conducive to the copper etching solution being used to etch more substrates, extending the replacement cycle of the copper etching solution to save costs, and also improving the problem of the etching speed being too fast and difficult to control.

[0043] The inorganic salt can play the purpose of regulating the etching speed of the copper-titanium metal film, and can improve the stability of repeated use of the copper etching solution for etching, that is, as the number of substrates etched by the copper etching solution increases, the side etch (S / E) can be reduced, and the side etch variation between each substrate is small, which ensures the etching effect and improves the etching efficiency. The amount of the inorganic salt is controlled at 0.05wt% to 3.00wt%, which can ensure a higher etching speed and avoid the problem of excessive etching of the copper-titanium metal film; if the content of the inorganic salt is less than 0.05wt%, the etching rate will be reduced and the sufficient etching speed cannot be achieved; if the content of the inorganic salt is greater than 3.00wt%, the photosensitive film used in the etching of the copper-titanium metal film may crack or the above-mentioned photosensitive film may peel off, and in the case where the above-mentioned photosensitive film cracks or peels off, the copper-titanium metal film located at the bottom of the photosensitive film may be over-etched.

[0044] The chelating agent can form a complex with the copper ions dissolved during the etching process through chelation, thereby adjusting the etching speed. The amount of the chelating agent is controlled at 0.05wt% to 5.00wt%, which can reliably complex the copper ions dissolved during etching, thereby ensuring the stability of the copper etching solution and ensuring a high etching efficiency to increase the frequency of repeated use of the copper etching solution, that is, the copper etching solution can be used to etch more substrates, and can also improve the residue and tailing problems formed due to the slow etching rate.

[0045] Fluoride can dissociate in water to release fluoride ions; fluoride can be used as an oxidant to regulate the etching speed of the titanium metal film. The fluoride content is controlled at 0.05wt% to 2.00wt%, which can ensure a higher etching speed of the titanium metal film and improve the overall etching rate that is too fast, resulting in obvious undercut phenomenon or etching damage to the lower Si layer, that is, it can improve the problem of etching damage to the glass substrate and the silicon layer.

[0046] The addition of stabilizer can reduce the surface tension of copper etching solution and improve etching uniformity; specifically, the stabilizer surrounds the copper ions dissolved into the copper etching solution by etching to suppress the activity of copper ions, thereby suppressing the decomposition reaction of hydrogen peroxide and ensuring the stability and uniformity of the etching process. The content of stabilizer is controlled at 0.05wt% to 10.00wt%, which not only improves the uniformity and stability of etching, but also can improve the problem of generating a large amount of foam during etching, and improve the safety of the etching process and the cleanliness of the etching environment.

[0047] The acid radical ions in sodium dodecylbenzenesulfonate have a relatively long alkyl chain, which can complex with copper ions and produce a good steric effect under the photoresist, weakening the exchange of the copper etchant under the photoresist and slowing down the lateral etching effect of the copper etchant on the metal, so as to ensure a small line width loss and a better cone angle. Sodium dodecylbenzenesulfonate can also improve the surface tension of the solution, thereby improving the wettability of the copper etchant on the substrate and the infiltration property of the high positions in the substrate structure, and then facilitating more effective control of the etching rate. Among them, controlling the content of sodium dodecylbenzenesulfonate at 0.05wt% - 1.00wt% can also improve the etching rate, reduce titanium residue while improving the problem that the etching rate is too fast to be controlled, resulting in an undercut phenomenon.

[0048] Controlling the pH of the copper etchant to be: 1.5 < pH ≤ 2 can ensure a high etching efficiency, improve the stability of the etchant, and will not cause problems of residue and tailing; and it can also improve the problem of sudden boiling of the copper etchant after repeated use of the copper etchant.

[0049] The preparation method of the copper etchant provided by the embodiment of the present invention only needs to mix each raw material in sequence, and the preparation method is simple and easy to operate.

[0050] The etching method provided by the embodiment of the present invention can recycle the copper etchant under preset temperature conditions. On the one hand, it can etch efficiently under the preset temperature conditions, and on the other hand, it can achieve the purpose of saving the amount of the etchant by recycling the copper etchant. Detailed implementation manners

[0051] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Those not specified in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments not specified in the manufacturer are all conventional products that can be obtained through commercial purchase.

[0052] The present invention provides a copper etchant, and the raw materials of the copper etchant include, by mass percentage:

[0053] 5.00wt% - 10.00wt% of hydrogen peroxide, for example: 5.00wt%, 6.00wt%, 7.00wt%, 8.00wt%, 9.00wt%, 10.00wt%, etc.;

[0054] 0.05wt% to 3.00wt% of a metal inhibitor, for example: 0.05wt%, 0.10wt%, 0.20wt%, 0.50wt%, 0.70wt%, 1.00wt%, 1.20wt%, 1.50wt%, 1.80wt%, 2.00wt%, 2.40wt%, 2.60wt%, 3.00wt%, etc.;

[0055] 5.00wt% to 15.00wt% of malonic acid, for example: 5.00wt%, 6.00wt%, 7.00wt%, 8.00wt%, 9.00wt%, 10.00wt%, 12.00wt%, 13.00wt%, 15.00wt%, etc.;

[0056] 0.05wt% to 3.00wt% of inorganic salt, for example: 0.05wt%, 0.10wt%, 0.20wt%, 0.50wt%, 0.70wt%, 1.00wt%, 1.20wt%, 1.50wt%, 1.80wt%, 2.00wt%, 2.40wt%, 2.60wt%, 3.00wt%, etc.;

[0057] 0.05wt% to 5.00wt% of a chelating agent, for example: 0.05wt%, 0.10wt%, 0.20wt%, 0.50wt%, 0.70wt%, 1.00wt%, 1.20wt%, 1.50wt%, 1.80wt%, 2.00wt%, 2.40wt%, 2.60wt%, 3.00wt%, 3.30wt%, 3.60wt%, 3.90wt%, 4.10wt%, 4.20wt%, 4.50wt%, 4.70wt%, 4.90wt%, 5.00wt%, etc.;

[0058] 0.05wt% to 2.00wt% of fluoride, for example: 0.05wt%, 0.10wt%, 0.20wt%, 0.50wt%, 0.70wt%, 1.00wt%, 1.20wt%, 1.50wt%, 1.80wt%, 2.00wt%, etc.;

[0059] 0.05wt% to 10.00wt% of a stabilizer, for example: 0.05wt%, 0.10wt%, 0.20wt%, 0.50wt%, 0.70wt%, 1.00wt%, 1.20wt%, 1.50wt%, 1.80wt%, 2.00wt%, 2.40wt%, 2.60wt%, 3.00wt%, 4.00wt%, 5.00wt%, 6.00wt%, 7.00wt%, 8.00wt%, 9.00wt%, 10.00wt%, etc.;

[0060] 0.05wt% to 1.00wt% of sodium dodecylbenzenesulfonate, for example: 0.05wt%, 0.10wt%, 0.20wt%, 0.50wt%, 0.70wt%, 1.00wt%, etc.;

[0061] The balance is water.

[0062] The hydrogen peroxide (H2O2) in the copper etching solution of the present embodiment is used as the main oxidant to promote the etching speed and maintain the stability of the etching solution. Compared with the mass of the copper etching solution as a whole of 100%, the content of hydrogen peroxide is relatively low, which is 5.00wt% to 10.00wt%, and can provide a suitable oxidation effect to ensure a good etching rate. If the content of hydrogen peroxide is lower than 5.00wt%, the etching rate will be too low and sufficient etching cannot be achieved. If the content of hydrogen peroxide is higher than 10.00wt%, the etching rate may be too fast and it is difficult to control the etching degree, and it is easy to cause the problem of over etching of the copper-titanium metal film. Moreover, by controlling the amount of hydrogen peroxide, the copper etching solution is a low hydrogen peroxide system, and the problem of rapid decomposition of hydrogen peroxide due to excessive copper ions, thereby causing the etching solution to heat up rapidly or even boil violently, will not occur.

[0063] The metal inhibitor can play a role in regulating the etching speed of the copper-titanium metal film, and can improve the stability of repeated use of the copper etching solution for etching, that is, as the number of substrates with metal wiring etched by the copper etching solution increases, the side etch (S / E) can be reduced, the process margin can be improved, the side etch variation between each substrate is small, and the etching effect is also guaranteed and the etching efficiency is improved. The content of the metal inhibitor is 0.05wt% to 3.00wt%, which can obtain a more suitable etching rate, improve the problem of over-etching caused by too fast etching rate, and also improve the problem of too slow etching rate and reduced efficiency. When the metal inhibitor is less than the above range, the etching rate of the copper-titanium metal film may become high and there is a problem of over-etching. When its content exceeds the above range, it will cause the copper etching rate to slow down, affecting the etching rate.

[0064] As an organic acid, malonic acid is beneficial to maintaining the target angle (cone angle) formed by the etching surface of the end of the copper wiring and the underlying substrate. Malonic acid contains two -COOH. When the first-order dissociation of malonic acid occurs, the generated -COO- will form an intramolecular hydrogen bond with another -COOH to stabilize the dissociation product, resulting in the first-order dissociation of malonic acid being relatively easier (pKa1=2.85), while the second-order dissociation has formed hydrogen bonds before the dissociation, so the difficulty of the second-order dissociation is increased (pKa2=5.70). In this way, the etching reaction rate can be slowed down by the step-by-step ionization of malonic acid, which is beneficial to maintaining the target angle (cone angle) formed by the etching surface of the end of the copper wiring and the underlying substrate. Malonic acid can also play the role of a co-oxidant, and the content is controlled at 5.00wt% to 15.00wt% to effectively control the etching rate; wherein, by adding malonic acid, the etched copper ions can be more easily dissolved in the copper etching solution, that is, the solubility of the copper ions is increased, which is conducive to making the copper etching solution can be used to etch more substrates, that is, to increase the frequency of repeated use of the copper etching solution, extend the replacement cycle of the copper etching solution, save costs, and improve the problem of the etching speed being too fast and difficult to control. If the content of malonic acid is lower than 5.00wt%, it is difficult to play the role of maintaining the etching shape, and the improvement of the solubility of the copper ions is limited, the frequency of repeated use of the copper etching solution is low, and the replacement cycle of the copper etching solution is short; if the content of malonic acid is higher than 15.00wt%, the pH of the copper etching solution as a whole is too low (pH is less than 1.5), which easily causes the etching rate to be too fast, and it is difficult to control the etching process.

[0065] Inorganic salts can selectively adsorb copper, thereby achieving the purpose of regulating the etching speed of the copper-titanium metal film, and can improve the stability of repeated use of copper etching solution for etching, that is, as the number of substrates etched by the copper etching solution increases, the side etching is reduced, and the side etching variation between each substrate is small, thereby ensuring the etching effect and improving the etching efficiency. If the content of inorganic salts is lower than 0.05wt%, the etching rate will be reduced and the sufficient etching speed cannot be achieved; if the content of inorganic salts is higher than 3.00wt%, the photosensitive film used in etching the copper-titanium metal film may crack or the above-mentioned photosensitive film may peel off, and in the case where the above-mentioned photosensitive film cracks or peels off, the copper-titanium metal film located at the bottom of the photosensitive film may be over-etched.

[0066] The chelating agent can form a complex with the copper ions dissolved during the etching process through chelation and inactivate it, thereby inhibiting the decomposition reaction of hydrogen peroxide in the etching solution to adjust the etching speed. The amount of the chelating agent is controlled at 0.05wt% to 5.00wt%, which can ensure a high etching efficiency on the one hand, and can reliably complex the copper ions formed by etching, so that the copper etching solution maintains a stable etching effect, thereby facilitating the increase in the frequency of repeated use of the copper etching solution, that is, the copper etching solution can be used to etch more substrates, and on the other hand, it can improve the residue and tailing problems formed due to the slow etching rate. In other words, if the amount of the chelating agent is less than 0.05wt%, after etching multiple substrates (for example, about 500 substrates) with the copper etching solution, a passivation film will be formed on the surface of the substrate, and a good etching effect cannot be achieved. It is also difficult to improve the etching efficiency, and the etching time becomes longer. In the same unit time, the number of substrates etched by the copper etching solution decreases, and the etching speed slows down, resulting in problems such as etching residue and tailing. If the amount of the chelating agent is greater than 5.00wt%, the copper ions are in an over-complexed state, the reaction rate is very fast, and the CD bias is large. As the etching base number increases, the copper complex ions in the etching solution increase, the reaction speed becomes faster, and the CD bias change is greater than 0.2μm, which is not conducive to product yield.

[0067] Fluoride can dissociate in water to release fluoride ions; fluoride can be used as an oxidant to regulate the etching speed of the titanium layer metal film to regulate the etching speed of the titanium layer metal film. The fluoride content is controlled at 0.05wt% to 2.00wt%, which can ensure a higher etching speed of the titanium layer metal film and improve the problem of the overall etching rate being too fast, resulting in obvious undercut phenomenon or etching damage (Damage) of the lower Si layer of the lower layer, that is, it can improve the problem of etching damage to the glass substrate and the silicon layer. If the fluoride content is lower than 0.05wt%, the oxidizing property of the copper etching solution is reduced, and the etching rate of the titanium layer is reduced; if the fluoride content is higher than 2.00wt%, the oxidizing property of the copper etching solution is improved as a whole, which will accelerate the etching rate of the titanium layer, and then easily lead to undercut phenomenon or etching damage (Damage) of the lower Si layer of the lower layer.

[0068] In a binary aqueous solution, the surface tension a is a function of the temperature T and the aqueous solution concentration c, i.e., a=f(c, T); at a certain temperature, the relationship between the surface tension and the solution concentration varies depending on the type of solute. If the solute is an inorganic substance, the surface tension increases with the increase of the solute concentration, while if the solute is an organic substance, the surface tension decreases with the increase of the solute concentration. The addition of a stabilizer is actually the addition of an organic substance, which can reduce the surface tension of the copper etching solution and improve the etching uniformity; wherein, the stabilizer surrounds the copper ions dissolved into the copper etching solution by etching to suppress the activity of the copper ions, thereby suppressing the decomposition reaction of hydrogen peroxide, and ensuring the stability and uniformity of the etching process. The content of the stabilizer is controlled within the range of 0.05wt% to 10.00wt%, which ensures the uniformity and stability of etching, improves the problem of a large amount of foam generated during the etching process, and improves the safety and cleanliness of the etching process; if the content of the stabilizer is lower than 0.05wt%, it is difficult to reduce the surface tension of the copper etching solution, and thus the uniformity of etching cannot be ensured, and the decomposition of hydrogen peroxide is accelerated, and thus it is difficult to maintain the stability of the copper etching solution, which easily leads to a shortened replacement cycle of the copper etching solution; if the content of the stabilizer is higher than 10.00wt%, the surface tension of the copper etching solution is too low, and a large amount of foam is easily generated during etching.

[0069] The acid radical ion in sodium dodecylbenzene sulfonate has a long alkyl chain, which can be complexed with copper ions and produce a good steric effect below the photoresist, weaken the exchange of copper etching solution below the photoresist, slow down the lateral etching effect of copper etching solution on the metal, to ensure that the smaller line width loss and the better cone angle appear. Sodium dodecylbenzene sulfonate can also improve the surface tension of the solution, even if the surface tension of the copper etching solution is reduced, thereby improving the wettability of the copper etching solution to the substrate and the impregnation of the high-position part in the substrate structure, and then facilitate more effectively controlling the etching rate. If the consumption of sodium dodecylbenzene sulfonate is less than 0.05wt%, the etching rate will be too fast, which is easy to cause undercut (undercut) phenomenon; if the consumption of sodium dodecylbenzene sulfonate is higher than 1.00wt%, it is easy to etch incompletely, resulting in the problem of titanium residue.

[0070] Optionally, the mass percentage of the metal inhibitor is 0.05wt% to 2.00wt%; the metal inhibitor can be adsorbed on the metal surface to form a thin film to buffer the etching speed. The amount controlled to be greater than 0.05wt% can further ensure a faster etching rate to improve efficiency. That is, if the content of the metal inhibitor is less than 0.05wt%, the etching rate of the copper-titanium metal film is too fast, and there is a problem of over-etching. If the content of the metal inhibitor is greater than 2.00wt%, it is easy to cause the etching rate of copper to be too slow, thereby reducing the etching efficiency.

[0071] Optionally, the mass percentage of the chelating agent is 0.05 wt% to 2.00 wt%. Compared with controlling the dosage of the chelating agent to be greater than 2.00 wt%, controlling the content of the chelating agent at 2.00 wt% and below can make the copper ions complex more reliably and efficiently, further improve the problem of reduced etching rate caused by the prolonged etching time, so as to more effectively reduce the etching residue of titanium and improve the tailing problem.

[0072] Optionally, the mass percentage of the stabilizer is 0.05 wt% to 8.00 wt%; compared with controlling the dosage of the stabilizer to be greater than 8.00 wt%, it can further avoid the generation of foam during the etching process, thereby ensuring the reliable progress of etching.

[0073] Optionally, the mass percentage of malonic acid is 6.00 wt%; in this way, the copper etching solution can exhibit the most suitable etching rate and can effectively adjust the taper angle of the copper-titanium metal film.

[0074] Optionally, the mass percentage of sodium dodecylbenzenesulfonate is 0.5 wt%; in this way, while ensuring that the copper etching solution has a relatively fast etching rate, it can effectively avoid the undercut phenomenon.

[0075] Optionally, the pH of the copper etching solution is: 1.5 < pH ≤ 2 (for example: 1.6, 1.7, 1.8, 1.9, 2, etc.). If the pH of the copper etching solution is lower than 1.5, the etching rate will be reduced, resulting in problems of residue or tailing; if the pH of the copper etching solution is greater than 2, it is easy to cause the instability of the copper etching solution, and as the number of processed sheets increases, that is, as the copper etching solution is reused multiple times, there is a risk of sudden boiling.

[0076] Optionally, the metal inhibitor includes at least one of 5-methyl-1H-tetrazole, 5-aminotetrazole, benzotriazole, tolyltriazole, pyrazole, pyrrole, imidazole, 2-methylimidazole, 2-ethylimidazole, 2-propylimidazole, 2-aminoimidazole, 4-methylimidazole, 4-ethylimidazole, and 4-propylimidazole.

[0077] Furthermore, the metal inhibitor includes at least one of 5-methyl-1H-tetrazole, 5-aminotetrazole, and benzotriazole.

[0078] Optionally, the inorganic salt includes at least one of ammonium bisulfate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, and dipotassium hydrogen phosphate.

[0079] Furthermore, the inorganic salts include ammonium bisulfate and ammonium dihydrogen phosphate. Through the combination of ammonium bisulfate and ammonium dihydrogen phosphate, the pH of the copper etching solution can be effectively controlled to be slightly acidic (1.5 < pH ≤ 2), so as to ensure the reliability of etching. That is, the above inorganic salts are all acid salts, which can ionize hydrogen ions to etch copper, thereby ensuring the reliability of etching.

[0080] Still further, the weight ratio of ammonium bisulfate to ammonium dihydrogen phosphate is 1:1 to 1:1.5 (for example: 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, etc.). The inventor further studies and finds that when malonic acid is contained in the copper etching solution, controlling the weight ratio of ammonium bisulfate to ammonium dihydrogen phosphate at 1:1 to 1:1.5 can achieve the optimal etching effect on the Cu, Ti alloy double-layer film. Among them, phosphate (i.e., ammonium dihydrogen phosphate) will selectively adsorb copper to inhibit galvanic corrosion by reducing the boundary corrosion potential between Cu and Ti, and adsorb to the surface of the boundary between the Ti layer and the next layer in contact with the Ti layer to inhibit undercut caused by crevice corrosion, which helps to improve the effect of process defects and can ensure a better surface profile of the copper-titanium alloy film. The above "next layer in contact with the Ti layer" can be IGZO (amorphous layer), Si layer, glass substrate, etc. in contact with the Ti layer.

[0081] Optionally, the chelating agent includes at least one of free asparagine, iminodiacetic acid, ethylenediaminetetraacetic acid, 2,4-imidazolidinedione, succinimide, glutarimide, glutamic acid, aspartic acid, pyroglutamic acid, and hippuric acid. Under acidic conditions, the chelating agent and copper ions form an equilibrium reaction: When the chelating agent is greater than or equal to 0.05 wt%, the reaction tends to proceed in the forward direction and the reaction rate is relatively fast, meeting the etching requirements. However, if the dosage of the chelating agent is greater than 5.00 wt%, the copper ions are in an over-complexed state, the reaction is too fast, which is not conducive to the yield.

[0082] Furthermore, the chelating agent includes at least one of iminodiacetic acid, ethylenediaminetetraacetic acid, and succinimide.

[0083] Optionally, the fluoride includes at least one of hydrofluoric acid, ammonium fluoride, ammonium bifluoride, sodium bifluoride, and potassium fluoride.

[0084] Furthermore, the fluoride includes at least one of ammonium fluoride and ammonium bifluoride.

[0085] Optionally, the stabilizer includes at least one of diethylene glycol, dipropylene glycol, 1,3-propanediol, 1,3-butanediol, 2,3-butanediol, 1,4-butanediol, and 1,5-pentanediol; the above stabilizer can ensure the stability of the etching solution while optimizing the etching process, improving product quality and production efficiency.

[0086] Further, the stabilizer includes at least one of diethylene glycol, dipropylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 2,3-butylene glycol and 1,4-butylene glycol.

[0087] Furthermore, the stabilizer includes at least one of diethylene glycol, dipropylene glycol and 1,4-butanediol; the above stabilizer can further improve the stability and uniformity of etching and ensure the etching effect and rate.

[0088] The present invention also provides a method for preparing a copper etching solution, which comprises: sequentially adding fluoride, an acidic composition, a metal inhibitor, a chelating agent, a stabilizer, water and hydrogen peroxide, and stirring; wherein the acidic composition comprises malonic acid, an inorganic salt and sodium dodecylbenzene sulfonate. The preparation method is simple and easy to operate.

[0089] The present invention also provides an etching method, which comprises: allowing the copper etching solution to be circulated and sprayed on the substrate to be etched under a preset temperature condition. In this way, on the one hand, efficient etching can be performed under the preset temperature condition, and on the other hand, the copper etching solution can be circulated to save the amount of etching solution.

[0090] Optionally, the preset temperature is 25° C. to 35° C., for example, 25° C., 30° C., 35° C., etc., which is not specifically limited here. It should be noted that different temperatures are selected for different substrates to ensure good etching efficiency and effect.

[0091] The present invention is further described in detail below in conjunction with embodiments.

[0092] The preparation method of each embodiment and comparative example is: add fluoride, acidic composition, metal inhibitor, chelating agent, stabilizer, water and hydrogen peroxide in sequence, and stir; wherein the acidic composition includes malonic acid, inorganic salt and sodium dodecylbenzene sulfonate. The raw materials of each embodiment and comparative example are shown in Tables 1 to 9 below.

[0093] Table 1

[0094]

[0095] Table 2

[0096]

[0097]

[0098] Table 3

[0099]

[0100] Table 4

[0101]

[0102]

[0103] Table 5

[0104]

[0105] Table 6

[0106]

[0107]

[0108] Table 7

[0109]

[0110] Table 8

[0111]

[0112]

[0113] Table 9

[0114]

[0115]

[0116] The copper etching solution of each embodiment and comparative example was used for etching test. Experimental conditions: 10L copper etching solution was added to the production line simulation cleaning equipment, the copper etching solution was kept at a constant temperature of 30°C, the spraying and circulating copper etching solution were turned on, and the temperature of the copper etching solution was stabilized at 30°C, and then a 10cm×10cm glass substrate (copper alloy film (Cu / Ti) was evaporated on the glass substrate, and a photoresist with a predetermined pattern was formed on the glass substrate by a photolithography process) was placed on the spray station, the test was started, sprayed for 100s, and the etching was completed. The substrate was transferred to the water spray station for cleaning. After the cleaning was completed, the sample was blown dry with an air knife, and the etching effect was confirmed under OM (optical microscope) and SEM (scanning electron microscope) (detecting the residue, tailing, and undercut of the etched copper-titanium alloy film).

[0117] 300ppm to 6000ppm of copper powder was added to the copper etching solution of each embodiment and comparative example to simulate the production line etching of several (roughly equivalent to 200) glass substrates to observe the change in side etch (S / E).

[0118] The test results are shown in Table 10.

[0119] Table 10

[0120]

[0121]

[0122]

[0123] The performance parameter evaluation criteria are as follows:

[0124] ①. The evaluation criteria for the S / E change amount according to the number of processed sheets are as follows:

[0125] ○: Excellent [S / E change amount ≤ 0.2 μm];

[0126] △: Good [0.2 μm < S / E change amount ≤ 0.3 μm];

[0127] ×: Poor [S / E change amount > 0.3 μm].

[0128] ②. The evaluation criteria for Remain are as follows:

[0129] ○: Excellent [Remain particle number ≤ 5];

[0130] △: Good [5 < Remain particle number ≤ 20];

[0131] ×: Poor [Remain particle number > 20].

[0132] ③. The evaluation criteria for titanium tail (Tail) are as follows:

[0133] ○: Excellent [Tail ≤ 0.1 μm];

[0134] △: Good [0.1 μm < Tail ≤ 0.2 μm];

[0135] ×: Poor [Tail > 0.2 μm].

[0136] ④. The evaluation criteria for undercut are as follows:

[0137] ○: Excellent [no undercut];

[0138] ×: Poor [with undercut].

[0139] By comparing Example 1, Example 2 with Comparative Example 1 and Comparative Example 2 according to Table 10, it can be seen that hydrogen peroxide (H2O2) as the main oxidant can regulate the etching rate. Among them, the dosages of hydrogen peroxide in Example 1 and Example 2 are the upper and lower limits of the formula. When the hydrogen peroxide is at the best mass percentage of 5wt% - 10wt%, the etching rate is slow when the content of hydrogen peroxide is lower than 5wt%, and the etching solution is prone to over-etching when the content is higher than 10wt%.

[0140] By comparing Example 4, Example 5, Example 6, Example 7, Example 22, Example 23, and Example 24 with Comparative Example 3, it can be seen that the metal inhibitor in the etching solution has a relatively large effect on the S / E change. Among them, the metal inhibitor in Example 4 and Example 5 is the best at an optimal dosage of 0.05wt% to 2.00wt%, and the S / E change is small; when the content of the metal inhibitor is lower than 0.05wt%, the S / E change is very large, and when the content is higher than 2wt%, the etching rate is slower, the residue becomes more, and the tailing becomes larger; by comparing Examples 4, 5 and 22-24, it can be seen that when the amount of the metal inhibitor is greater than 2.00wt%, the S / E change can also be controlled, but the change is larger than that of the embodiment with a metal inhibitor content of less than or equal to 2.00wt%.

[0141] Comparison of Example 8, Example 9 with Comparative Example 4, Comparative Example 5, and Comparative Example 6 shows that malonic acid has a relatively large effect on the S / E variation in the etching solution. + It can help dissolve copper ions and increase the life of the etching solution. If formic acid is added, as in Comparative Example 4, since formic acid is volatile, it may cause H + When the amount of malonic acid added is small, such as in Comparative Example 5, as the number of sheets processed increases, the copper ions in the etching solution increase, the etching rate slows down, and the S / E changes greatly. When the amount of malonic acid added is too large, such as in Comparative Example 6, the acid content is high. Since titanium is more active than copper, the etching rate of titanium is faster than copper, and undercut problems may occur. Comparing Examples 8, 9, and 10, it can be seen that when the content of malonic acid is less than or equal to 6wt%, the change in S / E decreases more significantly.

[0142] By comparing Example 10 and Example 11 with Comparative Example 7 and Comparative Example 8, it can be seen that when the mass ratio of ammonium hydrogen sulfate and ammonium dihydrogen phosphate in the inorganic salt is 1: (1 to 1.5), the etching solution can achieve excellent etching effect on Cu and Ti alloy double-layer films. In Comparative Example 7, the pH of ammonium dihydrogen phosphate in the etching solution system is relatively high, making the etching solution system alkaline, resulting in a slow etching rate when too much ammonium dihydrogen phosphate is added, and residues and large tailing will be produced. In Comparative Example 8, the acidity of hydrogen sulfate is stronger, and the addition of excessive ammonium hydrogen sulfate leads to too strong acidity and too large S / E change, resulting in defects.

[0143] By comparing Example 12, Example 13, Example 14, Example 15 with Comparative Example 9, Comparative Example 10, Comparative Example 11, Comparative Example 12, it can be seen that the chelating agent has a relatively large effect on the S / E variation. The chelating agent can form a complex with the copper ions dissolved during the etching process of the copper-titanium metal film in the copper etching solution composition through chelation, thereby adjusting the etching rate of the copper-based metal film. Embodiment 12 and embodiment 13 are the upper and lower limits of the formula, and the dosage of the chelating agent is optimally 0.05wt% to 2.00wt%. Among them, when the dosage of the chelating agent is 0.05wt% to 2.00wt%, even if the number of etched substrates exceeds 200 to about 500, a good etching effect can still be maintained, ensuring that the variation of S / E is controllable. When the content of the chelating agent is lower than 0.05wt%, the etching rate is slow and titanium residue problems may occur. When the content of the chelating agent is higher than 2.00wt%, as the number of processed substrates further increases (for example: when the number exceeds 200 to about 500, wherein Table 10 only shows the results of simulating the etching of about 200 substrates), the etching rate is accelerated and the variation of S / E is large.

[0144] The chelating agent and the copper and platinum alloy ions generated in the etching process form a chelate that is a reversible reaction. Comparing Example 28 and Example 13, it can be known that when the chelating agent is greater than 2.00wt% but not more than 5.00wt%, in the copper etching solution, as the number of etching panels increases, the copper ions in the etching solution increase. When the chelating agent content is high, the reaction is promoted to proceed in the forward direction, and the etching rate is accelerated. Compared with the chelating agent being less than 2.00wt% (such as Example 3), when the chelating agent is greater than 2.00wt% but not more than 5.00wt%, the S / E variation increases, and there is a certain risk of undercut, so it is more preferred that the amount of the chelating agent is 0.05wt% to 2.00wt%.

[0145] By comparing Example 16, Example 17, Example 18 with Comparative Example 13, Comparative Example 14, Comparative Example 15, it can be seen that fluoride has a relatively large impact on the S / E change and undercut. Fluoride is an oxidant that affects the etching speed of the titanium layer metal film and adjusts the etching speed of the titanium layer metal film. Example 16 and Example 17 are the upper and lower limits of the formula. When the fluoride content is 0.05wt% to 2.00wt% by mass, the best, when the fluoride content is lower than 0.05wt%, the etching speed is faster and the S / E change is larger. When the content is higher than 2wt%, obvious undercut occurs.

[0146] Comparing Example 19, Example 20, Example 21, Example 29 with Comparative Example 16, Comparative Example 17, Comparative Example 18, it can be seen that the stabilizer has a relatively large effect on the S / E variation. When the content of the stabilizer is less than 0.05wt%, as the number of processed substrates increases, the hydrogen peroxide decomposes very quickly, the S / E variation is large, and there is a risk of sudden boiling explosion if no stabilizer is added. When the content is higher than 10.00wt%, a large amount of foam is generated, affecting the etching uniformity, and there may be tailing at some locations and undercut at some locations; among them, in the embodiment where the stabilizer content is less than or equal to 8.00wt%, the improvement of tailing is more obvious.

[0147] By comparing Example 3 and Example 25 with Comparative Examples 19 and 20, it can be seen that sodium dodecylbenzene sulfonate has a relatively large effect on tailing and undercut. When the content of sodium dodecylbenzene sulfonate is lower than 0.05wt%, the etching rate is too fast, resulting in undercut. When the content is higher than 1.00wt%, titanium residue is caused. Among them, when the content of sodium dodecylbenzene sulfonate is 0.5wt%, the improvement of titanium residue is most obvious.

[0148] In summary, the copper etching solution of the present invention can be used to etch a composite film layer of copper and titanium, has good stability, can form a good etching profile by etching, can also improve the problems of incomplete etching, titanium residue and titanium tailing, and is not easy to damage the glass base and the silicon layer; the preparation method of the copper etching solution is simple and easy to operate; the etching method of the copper etching solution can efficiently perform etching and can save the amount of etching solution; and, by adopting a low hydrogen peroxide system, the problem of rapid decomposition of hydrogen peroxide due to excessive copper ions, thereby causing rapid heating or even violent boiling of the etching solution, will not occur.

[0149] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A copper etching solution, characterized in that The raw materials of the copper etching solution include, by mass percentage: 5.00wt% to 10.00wt% of hydrogen peroxide; 0.05wt% to 3.00wt% of metal inhibitor; 5.00wt% to 15.00wt% of malonic acid; 0.05wt% to 3.00wt% of inorganic salt; 0.05wt% to 5.00wt% of chelating agent; 0.05wt% to 2.00wt% of fluoride; 0.05wt% to 10.00wt% of stabilizer; 0.05wt% to 1.00wt% of sodium dodecylbenzene sulfonate; the balance is water; The pH of the copper etching solution is: 1.5 <pH≤2。 2. The copper etching solution according to claim 1, characterized in that The mass percentage of the metal inhibitor is 0.05wt% to 2.00wt%; and / or, The mass percentage of the chelating agent is 0.05wt% to 2.00wt%; and / or, The mass percentage of the stabilizer is 0.05wt% to 8.00wt%; and / or, The mass percentage of the malonic acid is 6.00wt%; and / or, The mass percentage of the sodium dodecylbenzene sulfonate is 0.5wt%.

3. The copper etching solution according to claim 1, characterized in that The metal inhibitor comprises at least one of 5-methyl-1H-tetrazole, 5-aminotetrazole, benzotriazole, tolyltriazole, pyrazole, pyrrole, imidazole, 2-methylimidazole, 2-ethylimidazole, 2-propylimidazole, 2-aminoimidazole, 4-methylimidazole, 4-ethylimidazole and 4-propylimidazole; and / or, The inorganic salt comprises at least one of ammonium hydrogen sulfate, ammonium dihydrogen phosphate, disodium hydrogen phosphate and dipotassium hydrogen phosphate; and / or, The chelating agent comprises at least one of free asparagine, iminodiacetic acid, ethylenediaminetetraacetic acid, 2,4-imidazolidinedione, succinimide, glutarimide, glutamic acid, aspartic acid, pyroglutamic acid and hippuric acid; and / or, The fluoride comprises at least one of hydrofluoric acid, ammonium fluoride, ammonium bifluoride, sodium bifluoride and potassium fluoride; and / or, The stabilizer includes at least one of diethylene glycol, dipropylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 1,4-butylene glycol and 1,5-pentanediol.

4. The copper etching solution according to claim 3, characterized in that The inorganic salt includes the ammonium hydrogen sulfate and the ammonium dihydrogen phosphate.

5. The copper etching solution according to claim 4, characterized in that The weight ratio of the ammonium hydrogen sulfate to the ammonium dihydrogen phosphate is 1:1 to 1:1.

5.

6. The copper etching solution according to claim 3, characterized in that The metal inhibitor comprises at least one of the 5-methyl-1H-tetrazole, the 5-aminotetrazole and the benzotriazole; and / or, The chelating agent includes at least one of the iminodiacetic acid, the ethylenediaminetetraacetic acid and the succinimide; and / or, The fluoride comprises at least one of the ammonium fluoride and the ammonium bifluoride; and / or, The stabilizer includes at least one of the diethylene glycol, the dipropylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, and 1,4-butylene glycol.

7. The copper etching solution according to claim 6, characterized in that The stabilizer includes at least one of the diethylene glycol, the dipropylene glycol, and 1,4-butanediol.

8. The method for preparing a copper etching solution according to any one of claims 1 to 7, wherein: include: The fluoride, the acidic composition, the metal inhibitor, the chelating agent, the stabilizer, the water and the hydrogen peroxide are added in sequence and stirred; wherein the acidic composition includes the malonic acid, the inorganic salt and the sodium dodecylbenzene sulfonate.

9. An etching method, characterized in that: include: The copper etching solution according to any one of claims 1 to 7 is circulated and sprayed on the substrate to be etched under a preset temperature condition.

10. The etching method according to claim 9, characterized in that: The preset temperature is 25°C to 35°C.

Citation Information

Cited By

  • Etching solution for AMB active metal brazing material etching process and horizontal line etching method thereof

    CN120945370A

  • F-free one-dosage type low IGZO damage metal etching liquid and preparation method thereof

    CN121759955A

  • F-free low-igzo damage metal etching solution and preparation method thereof

    CN121759955B